Load Carrying Capacity Analysis of Helicoidal Surface Thrust Bearing - Zhang Wentao; Zhang Songlin; Cheng Baixin (Jixie chuandong)
The different structural helicoidal surface thrust bearing lubrication models is built and calculated with FLUENT to analyze the effects of the thickness of the oil film,pitch of the helicoidal surface and angular speed on load capacity of the thrust bearing,which provide the theoretical basis for design of helicoidal surface thrust bearing. The results show that with the increase of the pitch and oil film thickness,the maximum temperature of the oil film is decreased. The axial load capacity decreases with the increase of the oil film thickness.There is an ratio of pad height to the minimum film thickness which maximizes the load capacity when the minimum thickness of oil film and angular speed are constant,the best ratio of pad height to the minimum film thickness is 1. 4. The maximum temperature and load capacity of the oil film are linearly related to the angular speed. The load capacity of the helicoidal surface is much higher than the flat.